Trajectories for mining space mission on asteroids in near-Earth orbit - Vieira Neto, Ernesto [UNESP]; Pires, Pryscilla; Giuliatti Winter, Silvia [UNESP] (Springer Nature, 2023)
Mining asteroids will soon be a reality; the technology for this venture is almost off the shelf depending on the development of artificial intelligence for autonomous robotic spacecraft. In this work, we treat the problem of transporting ores to Earth, mainly to the vicinity of the Moon to avoid any accident of a colliding asteroid. We explore the database for near-Earth objects (NEOs) and choose the best asteroid candidates for mining, based on their orbit. We studied Apollos and Atens groups since they are Earth orbit crossing objects. The main strategy of this work is to obtain trajectories that could lead to a transfer orbit from the current orbit of the asteroid to the vicinity of the lunar orbit. We use the relative two body energy between the Moon and the asteroid to find the best orbit candidates. The best point of the asteroid trajectory is the point that could lead to a less expensive maneuver. We found that there are less than 1 000 asteroids from the Apollo group, and less than 350 asteroids from the Aten group, which could be transferred to a temporary orbit around the Moon with a variation in velocity smaller than 447 m/s. We found a temporary capture of an Apollo asteroid (2015 DO215) around the Moon in the year ∼ 2063 . We also identified, from our numerical simulations, that an asteroid of the Aten group may collide with Earth. Therefore, we propose two mitigation maneuvers to change the probability of collision.